Intermittent Growth of a Newly-Born Volcanic Island and Its Feeding System Revealed by Geological and Geochemical Monitoring 2013–2020, Nishinoshima, Ogasawara, Japan - Maeno, Fukashi; Yasuda, Atsushi; Hokanishi, Natsumi; Kaneko, Takayuki; Tamura, Yoshihiko; Yoshimoto, Mitsuhiro; Nakano, Shun; Takagi, Akimichi; Takeo, Minoru; Nakada, Setsuya (Frontiers in Earth Science, 2021)
The island-forming Nishinoshima eruptions in the Ogasawara Islands, Japan, provide a rare opportunity to examine how the terrestrial part of Earth’s surface increases via volcanism. Here, the sequence of recent eruptive activity of Nishinoshima is described based on long-term geological and geochemical monitoring of eruptive products. Processes of island growth and temporal changes in the magma chemistry are discussed. The growth of Nishinoshima was sustained by the effusion of low-viscosity andesite lava flows since 2013. The lava flows spread radially with numerous branches, resulting in compound lava flows. Lava flows form the coherent base of the new volcanic edifice; however, pyroclastic eruptions further developed the subaerial volcanic edifice. The duration of three consecutive eruptive episodes decreased from 2 years to a week through the entire eruptive sequence, with a decreasing eruptive volume and discharge rate through time. However, the latest, fourth episode was the most intense and largest, with a magma discharge rate on the order of 106 m3/day. The temporal change in the chemical composition of the magma indicates that more mafic magma was involved in the later episodes. The initial andesite magma with ∼60 wt% SiO2 changed to basaltic andesite magma with ∼55 wt% SiO2, including olivine phenocryst, during the last episode. The eruptive behavior and geochemical characteristics suggest that the 2013–2020 Nishinoshima eruption was fueled by magma resulting from the mixing of silicic and mafic components in a shallow reservoir and by magma episodically supplied from deeper reservoirs. The lava effusion and the occasional explosive eruptions, sustained by the discharge of magma caused by the interactions of these multiple magma reservoirs at different depths, contributed to the formation and growth of the new Nishinoshima volcanic island since 2013. Comparisons with several examples of island-forming eruptions in shallow seas indicate that a long-lasting voluminous lava effusion with a discharge rate on the order of at least 104 m3/day (annual average) to 105 m3/day (monthly average) is required for the formation and growth of a new volcanic island with a diameter on km-scale that can survive sea-wave erosion over the years.